2011
DOI: 10.1073/pnas.1015605108
|View full text |Cite
|
Sign up to set email alerts
|

Repulsive guidance molecule-A (RGM-A) inhibits leukocyte migration and mitigates inflammation

Abstract: Directed cell migration is a prerequisite not only for the development of the central nervous system, but also for topically restricted, appropriate immune responses. This is crucial for host defense and immune surveillance. Attracting environmental cues guiding leukocyte cell traffic are likely to be complemented by repulsive cues, which actively abolish cell migration. One such a paradigm exists in the developing nervous system, where neuronal migration and axonal path finding is balanced by chemoattractive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
53
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 55 publications
(58 citation statements)
references
References 33 publications
5
53
0
Order By: Relevance
“…Instead, as RGMa-neogenin cell spreading was enhanced by Noggin treatment, we report an unexpected deregulating activity of BMP. Our results are consistent with a model whereby BMP activity is not necessary for RGManeogenin function, as reported recently in the immune system (34). It remains to be determined whether RGMa interacts with neogenin in cis or in trans to mediate cell adhesion.…”
Section: Discussionsupporting
confidence: 81%
“…Instead, as RGMa-neogenin cell spreading was enhanced by Noggin treatment, we report an unexpected deregulating activity of BMP. Our results are consistent with a model whereby BMP activity is not necessary for RGManeogenin function, as reported recently in the immune system (34). It remains to be determined whether RGMa interacts with neogenin in cis or in trans to mediate cell adhesion.…”
Section: Discussionsupporting
confidence: 81%
“…These experiments suggest that blocking RGMa may reduce inflammatory disease. However, another study reported that RGMa inhibits migration of RGMa-expressing leukocytes (T and B lymphocytes, monocytes, and granulocytes) via chemo-and contact repulsion and RGMa suppressed inflammation in a zymosan-induced peritonitis model [33]. These seemingly contrasting results might be explained by the different types of models used and by differences in underlying signaling complexes.…”
Section: Immune Cell Signaling and Multiple Sclerosismentioning
confidence: 99%
“…These data show that RGMs are a structural bridge between Neogenin and BMP signaling, and inform that a clustering mechanism may be important in the activation of these signaling pathways. [29,30], early stages of neurulation [31], CD4+ T cell adhesion and activation [32], and leukocyte migration [33]. This can be either contact dependent (adhesive) or mediated by gradients established by cleaved extracellular RGM isoforms.…”
Section: Structural Insight Into Ligand-receptor Interactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1][2][3] Thought to be exclusively expressed in the central nervous system (CNS), RGMa has been recently found to be expressed in spleen, monocytes, and lymphocytes, which suggests a role within the immune system. 4 Futhermore, a study on multiple sclerosis (MS) and a mouse model of myelin oligodendrocyte glycoprotein (MOG)-induced experimental autoimmune encephalomyelitis (EAE), in which dendritic cells (DCs) play an irreplaceable role, demonstrates that application of a RGMa-neutralizing antibody can reduce the clinical signs and immune responses of EAE by DCs. 5 Consistent with the study, we found that the expression of RGMa was induced in mature DCs.…”
Section: Introductionmentioning
confidence: 99%